Sosialisasi dan Edukasi Kepemimpinan Transformasional Berbasis Karakter untuk Penguatan Nilai Pancasila - Siti Marwiyah; Nurul Jannah Lailatul Fitria; Yungky Andik Pradana (Jurnal Pengabdian Masyarakat (abdira), 2022)
An ideal leader is needed for Indonesia. Students as the next generation of the nation will certainly inherit the previous leadership. Students are not only prepared as academics who are studying but are also prepared to go directly to the community. Especially for graduates of social science and political science. Students can apply their knowledge and experience in the environment actively. However, not all students understand the basics of leadership, so it is important to be socialized so that all students can apply the basics of transformational leadership. Community service through socialization and Character-Based Transformational Leadership Education for Strengthening Pancasila Values is carried out at Panca Marga University. The socialization activity was carried out in the pre-event stage with coordination in the Whatsapp group, socialization and question and answer events, and after the event distributing flyers and e-books of socialization materials. The results that can be conveyed from the socialization and education activities are that students understand about character transformational leadership, especially in Indonesia by applying the values of Pancasila.